Active Teaching Methods: Personal Experience of Integrating Spiritual and Moral Values - Tengku Kasim, T.S.A.; Yusmini, M.Y. (Taylor & Francis, 2014)
Islamic education has always recognized spiritual and moral values as significant elements in developing a “balanced” human being. One way of demonstrating spiritual and moral concepts is through effective teaching methods that integrate and forefront these values. This article offers an investigation of how the authors’ teaching approaches integrate spiritual and moral values in tertiary/university curriculum subjects as part of the students’ spiritual and moral development.